Basal and postprandial intermediary metabolism in high altitude and sea level obese patients - Garmendia-Lorena, Fausto (2019)
Objectives: To study the basal and postprandial intermediary metabolism of obese high altitude dwellers (OHAD), and to compare with the intermediary metabolism of normal high altitude dwellers (NHAD) and with obese of sea level dwellers (OSLD). Methods: A total of 30 NHAD, 39 OHAD (Cusco, Perú, at 3395 meters above the sea level) and 35 OSLD (Lima, Perú, at 150 meters above the sea level), of both genders, 40 to 70 years old were included. Glucose (G), total cholesterol (TC), HDL cholesterol (HDL), triglycerides (Tg), insulin (I) and non-esterified fatty acids were measured in blood at fasting, Cholesterol VLDL,LDL, NOHDL and HOMA coefficient were calculated; thereafter and during 6 hours after ingestion of a standardizedmixed meal G, I, Tg and NEFA were determined in blood. Results: At fasting HAOD had lower HDL and higher Tg and NEFA concentrations than HAND and higher NEFA than OSLD. During the postprandial period HAOD presented higher values of I, Tg and NEFA than HAN and higher values of Tg and NEFA than SLO with minor differences in G and I. Conclusions: HAO subjects in comparison to HAN present resistance to insulin and in relation to SLO higher values of Tg and NEFA.